Chicoric acid promotes glucose uptake and Akt phosphorylation via AMP-activated protein kinase α-dependent pathway. (August 2019) - Peng, Ye; Sun, Quancai; Park, Yeonhwa
Graphical abstract: Highlights: Chicoric acid promotes glucose uptake in cell and mice model. Chicoric acid increases Akt phosphorylation. The effects of chicoric acid on glucose uptake and Akt are dependent upon AMPKα. Abstract: Chicoric acid is a naturally-occurring dicaffeoyl ester often found in chicory. Based on previous studies chicoric acid ameliorated insulin resistance in human hepatoma cells, the current study was undertaken to investigate the effects of chicoric acid on glucose homeostasis in C2C12 myotubes and male C57BL/6J mice. Chicoric acid (25 µM) significantly enhanced glucose uptake and the phosphorylation of protein kinase B (Akt) independent of insulin in C2C12 myotubes. Consistently, glucose tolerance was improved in mice after 5-day oral administration of chicoric acid. Chicoric acid significantly increased the phosphorylation of 5′-AMP-activated protein kinase α (AMPKα), which is known to activate Akt, independent of insulin, via increasing the AMP/ATP ratio in C2C12 myotubes. The above effects of chicoric acid were abolished by an inhibition of AMPKα through Compound C (an AMPKα inhibitor) or AMPKα knockout. Collectively, these results suggest that chicoric acid promotes glucose uptake insulin-independently via an AMPKα-mediated pathway.